E-Commerce For Village Information System Using Agile Methodology - Leni Fitriani; Prayoga Hakim; R. Mujahid Al Haq (Department of Informatics, UIN Sunan Gunung Djati Bandung, 2022)
With the entry into the era of Industrial Revolution 4.0, the development of digitization of various aspects at the village level began. The level of use of mobile devices in the commercial transactions of society is now a massive number of users. It happens not only in large transactions but also in small transactions. With the community's high interest in the use of smartphone devices, this is a different opportunity to explore the potential of each village by helping the community, tiny and medium enterprises in conducting transactions, sales, and marketing online through the village government website. The village information system itself requires an e-commerce feature on its page to help small and medium enterprises in the area to sell products online through a simple page display. This research aims to design and develop new features of the village system that plays a role in the field of e-commerce with the Direct Message transaction method. The system development methodology used is Agile with Scrum as a framework. The Agile Model is a short-term development model that requires rapid adaptation and development to changes in any form. This e-commerce feature is for local communities, especially Micro, Small, and Medium Enterprises, so their products' marketing reach is even more outstanding while being recorded in the village system.